THE EFFORTS OF DIKMAS LANTAS IN TRAFFIC ACCIDENT PREVENTION TO SUPPORT SECURITY, SAFETY, AND TRAFFIC SUCCESS IN POLRES MAGELANG - rosyade ariq fepiosandi (Police Studies Review, 2022)
The number of victims of traffic accidents in Magelang Regency in 2021 was 1692 people, an increase of 3.6% when compared to 2020 of 1633 people. The process of increasing the number of victims illustrates that during the COVID-19 pandemic, the trend of the number of victims of traffic accidents in Magelang Regency tends to increase. Traffic problems are included on a national scale which develops along with the development of society. The problem faced today is the high number of traffic accidents on the highway. Therefore, this study aims to describe the implementation of public education in the prevention of traffic accidents in order to support security safety order smooth traffic at the Magelang Police and to describe the efforts of the then social and community education in preventing traffic accidents in order to support security safety order smooth traffic at the Magelang regency. The theory used in this research is the SWOT Theory initiated by Sondang P Siagian and Management Theory initiated by George R. Terry. The concept used is the concept of effort, the concept of public education in the Traffic Sector, and the concept of traffic accidents. The research approach used is a qualitative approach with the type of field study research. The research was conducted in the Magelang Regency, Central Java Province. The results of the study indicate that in general the implementation of public education in the Traffic Sector in preventing traffic accidents at the Magelang Police Station, which was still lacking, has increased with efforts in the field. However, there are still some obstacles, such as the lack of human resources and the absence of competency certification for the tasks of the previous education and community education. In addition, public education efforts in the Traffic Sector in preventing traffic accidents at the Magelang Police Station are still considered less than optimal, especially during the COVID-19 pandemic, many schools were closed due to the rising number of COVID-19, the Magelang Police chose to eliminate coaching and counseling activities. regarding traffic order, even though you can use other media such as online socialization through Youtube or Zoom Meetings, so that coaching and counseling activities about traffic order can still be carried out without face-to-face and physical contact.